Occlusal Plane, Mandibular Position and Dentoalveolar Changes during the Orthodontic Treatment with the Use of Mini-Screws - Julián David Gómez-Bedoya; Pablo Arley Escobar-Serna; Eliana Midori Tanaka-Lozano; Andrés A. Agudelo-Suárez; Diana Milena Ramírez-Ossa (Dentistry Journal, 2024)
This study aimed to describe the changes produced on the occlusal plane (OP), the mandibular position and the dentoalveolar compensations of patients with distalization of the maxillary/mandibular arch assisted by mini-screws (MS). A descriptive case–series study was performed using the digital lateral cephalograms (DLC) of nine patients who underwent orthodontic treatment and required the use of MS for a complete distalization of the maxillary/mandibular arch. Records were collected at three different times (T1–T2–T3) and digitally analyzed (variables: Skeletal diagnosis; maxillary occlusal plane; position of the maxilla/mandible; and dentoalveolar changes of the distalization arch tracing the longitudinal axis of incisors/molars regarding the palatal/mandibular plane). Findings show that the OP varied from T1–T2–T3 in all cases, indicating its stepping or flattening. ODI, APDI, SNA, SNB, and ANB changed minimally in all cases, without variations in the mandibular position or in the skeletal diagnosis. Dentoalveolar measurements also showed differences between T1–T2–T3. In summary, conventional orthodontic treatment modified the OP during the first phase of treatment. Moreover, the distalization mechanics with MS changed the OP and produced dentoalveolar changes, mainly in the inclination of incisors and molars. Other measures considered in the study did not change substantially.